Upaya Penyuluhan Kesehatan Tentang Terapi Herbal Kayu Manis sebagai Alternatif Penurunan Glukosa Darah pada Lansia - Muhamad Iqbal Sutisna; Rani Puspita; Ade Lulu; Astriani Hapsari; Grace Angeliqch; Intan Jesica (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion, insulin action, or both. The global prevalence of diabetes continues to increase and contributes significantly to morbidity and cardiovascular complications. In addition to pharmacological therapy, the use of herbal-based complementary therapies has gained public interest. Cinnamon (Cinnamomum spp.) is a widely studied herbal plant containing active compounds such as cinnamaldehyde, polyphenols, and flavonoids, which have potential antihyperglycemic effects through improving insulin sensitivity and glucose metabolism. However, public understanding regarding proper usage, safety limits, and scientific evidence of cinnamon utilization remains limited. This community-based health education activity aimed to improve knowledge and understanding of cinnamon as a complementary therapy for diabetes mellitus. The activity was conducted through health education sessions using lectures, posters, leaflets, and interactive discussions targeting patients with diabetes mellitus and individuals at risk. Evaluation results indicated an increase in participants’ understanding of the benefits, active compounds, safe dosage, and limitations of cinnamon use. The findings suggest that health education effectively enhances community knowledge regarding evidence-based herbal utilization. Cinnamon can be safely used as a complementary therapy when consumed within recommended doses and under health professional supervision, but it should not replace standard antidiabetic treatment.